Middle Cenozoic penguin remains from the Patagonian cordillera - Acosta Hospitaleche, Carolina Ileana Alicia (2013)
Middle Cenozoic marine fossil-bearing beds crop out in the Cerro Plataforma (western Chubut Province, Argentina) at about 1,400 m a.s.l. They are located 500 km far from the modern Atlantic coast and only 50 km from the Pacific Ocean. Well preserved penguin bones and a shark tooth were found therein. Invertebrates include corals, bryozoans, abundant mollusks, echinoids, and crabs. Morphogeometric analysis and comparative description confirmed that the penguin humerus is referable to Palaeospheniscus bergi Moreno and Mercerat, 1891. Most of the fossils indicate a Miocene age. However, there is a debate about if the bearing beds are of Pacific or Atlantic origin. Fossil invertebrates identifiable at species level reveal Pacific affinity, the shark species is cosmopolitan, and Palaeospheniscus bergi is known from early Miocene Atlantic units of southern South America. Yet, Palaeospheniscus Moreno and Mercerat, 1891 is also known from Miocene Pacific beds but it has not been identified at specific level yet. This is the highest site in topographic terms in which penguin fossils occur. This indicates a remarkable uplift for the area, probably from the middle Miocene.